2013
DOI: 10.1038/ncomms2581
|View full text |Cite|
|
Sign up to set email alerts
|

Perilipin1 promotes unilocular lipid droplet formation through the activation of Fsp27 in adipocytes

Abstract: Mature white adipocytes contain a characteristic unilocular lipid droplet. However, the molecular mechanisms underlying unilocular lipid droplet formation are poorly understood. We previously showed that Fsp27, an adipocyte-specific lipid droplet-associated protein, promotes lipid droplet growth by initiating lipid exchange and transfer. Here, we identify Perilipin1 (Plin1), another adipocyte-specific lipid droplet-associated protein, as an Fsp27 activator. Plin1 interacts with the CIDE-N domain of Fsp27 and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
221
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(241 citation statements)
references
References 56 publications
(86 reference statements)
9
221
0
2
Order By: Relevance
“…In a prior work, we found that leptin constitutes a positive regulator of fat browning process through the upregulation of Prdm16, Ucp1, and Cidec in murine subcutaneous adipocytes 71 . Accordingly, leptin deficiency was associated with a downregulation of Prdm16, a zinc-finger protein involved in the expression of brown fat-selective genes, and Ucp1, a brown-and beige-specific marker, together with an upregulation of Cidec, which promotes lipid droplet formation in subcutaneous AT 72 , suggesting an impaired fat browning in the context of leptin deficiency. Interestingly, the deletion of iNOS upregulated Prdm16 mRNA levels and tended to increase Ucp1 transcript levels.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior work, we found that leptin constitutes a positive regulator of fat browning process through the upregulation of Prdm16, Ucp1, and Cidec in murine subcutaneous adipocytes 71 . Accordingly, leptin deficiency was associated with a downregulation of Prdm16, a zinc-finger protein involved in the expression of brown fat-selective genes, and Ucp1, a brown-and beige-specific marker, together with an upregulation of Cidec, which promotes lipid droplet formation in subcutaneous AT 72 , suggesting an impaired fat browning in the context of leptin deficiency. Interestingly, the deletion of iNOS upregulated Prdm16 mRNA levels and tended to increase Ucp1 transcript levels.…”
Section: Discussionmentioning
confidence: 99%
“…Both CIDEA and CIDEC catalyse a slow fusion mechanism in which a donor LD transfers its content to a larger LD in a process driven by their internal pressure gradient [34]. CIDE proteins stabilize LD pairs by the formation of trans homodimers at the LD-LD contact site [19, 34,35], where they facilitate the transport of neutral lipids through the phospholipid monolayer. The lipid transfer step requires the presence of a cationic amphipathic helix, which by interacting with PA could interfere with the phospholipid barrier to increase its permeability to TAG [19].…”
Section: Ld-ld Fusionmentioning
confidence: 99%
“…The lipid transfer step requires the presence of a cationic amphipathic helix, which by interacting with PA could interfere with the phospholipid barrier to increase its permeability to TAG [19]. CIDEC activity is enhanced and regulated by accessory proteins such as PLIN1 and Rab8a [35,36]. However, CIDE proteins alone are probably sufficient to fulfil the full process as the expression of murine CIDEA in yeast produces LD enlargement despite these organisms lacking CIDE homologues and therefore are unlikely to present functional interactors [19].…”
Section: Ld-ld Fusionmentioning
confidence: 99%
“…One is growth of LD itself and the other is fusion of the LDs. FSP27 is proposed to promote LD growth by the latter mechanism by which it is focally enriched at the contact site between LDs and assumed to mediate the fusion of contacted LDs through their dimerization [17,18]. However, the clarification of molecular mechanism responsible for this process is still not sufficient.…”
Section: Discussionmentioning
confidence: 99%